Implementasi Gerakan Literasi Nasional (GLN) Di Kabupaten Lombok Tengah: Hambatan Guru SD dalam Membelajarkan Literasi Dasar Selama Masa Pandemi - Muhammad Erfan; Arif Widodo; Umar Umar; Aisa Nikmah Rahmatih (IKIP Siliwangi, 2022)
This study aims to describe the readiness of elementary school teachers and identify the obstacles faced by teachers in teaching basic literacy skills during the COVID-19 pandemic in 4 (four) areas in Central Lombok Regency. The areas studied are Selebung Village, Batukliang District, Setiling Village, North Batukliang District, Darek Village, Southwest Praya District, and Kuta Village, Pujut District, all of which are located in Central Lombok Regency, NTB. This study is qualitative research in which data were obtained from interviews with elementary school teachers in 4 (four) areas in Central Lombok. The data obtained were then described and analyzed descriptively. The results showed that educators or teachers experienced several obstacles in teaching basic literacy skills in elementary schools in Central Lombok during the pandemic. The obstacles faced by these educators include limited learning media and teaching materials, ineffective learning time, and a less supportive learning atmosphere, many educators are bothered by many other activities, it is difficult to motivate students to learn, as well as from the realm of evaluation, educators have limitations in providing instruments or tools for evaluating learning outcomes, especially basic literacy skills.